What is this thing called happiness? - Feldman, Fred, 1941- (Oxford : Oxford University Press, 2010)
Fred Feldman presents a study of the nature and value of happiness. He offers critical discussions of the main philosophical and psychological theories of happiness, and a presentation and defense of his own theory of happiness.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Happiness -- Philosophy